1974
DOI: 10.1002/bit.260160105
|View full text |Cite
|
Sign up to set email alerts
|

Interactions in a mixed bacterial population growing on methane in continuous culture

Abstract: SummaryThe growth of a mixed methane-utilizing culture in a continuous flow fermenter has been studied under both methane and oxygen limitation. Small additions of methanol have been shown to inhibit the methane-utilizing moiety in the culture and it has been shown that the Hyphomicrobium sp. in the mixed culture removes any inhibitory methanol. The interaction between the methane-utilizing Pseudomonas sp., and the Hyphomicrobium sp. has been explained and a model of the continuous mixed culture under oxygen l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(72 citation statements)
references
References 12 publications
(2 reference statements)
3
69
0
Order By: Relevance
“…Positive cell-cell interactions involving methylotrophic bacteria have been reported previously for aerobic species. For example, Wilkinson et al ( 1974) demonstrated that growth of aerobic mixed cultures on methane was enhanced as the result of removal of toxic methanol by a Hyphomicrobium species which was produced by a methane-oxidizing Pseudomonas species.…”
Section: Discussionmentioning
confidence: 99%
“…Positive cell-cell interactions involving methylotrophic bacteria have been reported previously for aerobic species. For example, Wilkinson et al ( 1974) demonstrated that growth of aerobic mixed cultures on methane was enhanced as the result of removal of toxic methanol by a Hyphomicrobium species which was produced by a methane-oxidizing Pseudomonas species.…”
Section: Discussionmentioning
confidence: 99%
“…Methanotrophic bacteria are often contaminated with methanol-oxidizing Hyphomicrobium sp. strains which profit from some excreted methanol and help protect the methanotroph by decreasing possibly toxic methanol concentrations (Wilkinson et al 1974). Perhaps also formaldehyde is removed this way which is far more toxic than methanol.…”
Section: Types Of Cooperation Among Microorganismsmentioning
confidence: 99%
“…In this way, they create opportunity for new ecological interactions to emerge (Phelan et al, 2012). The spectrum of interactions that results from this process includesbesides the competition for limiting resources (Foster and Bell, 2012) or the release of toxic (waste) products (Wilkinson et al, 1974)-also interactions, in which one organism benefits from the biochemical activities of another one. For example, a metabolic by-product that is released by one genotype can benefit a recipient strain that utilises this resource (Rosenzweig et al, 1994;Doebeli, 2002).…”
Section: Introductionmentioning
confidence: 99%